EFEKTIVITAS STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) DALAM PEMBELAJARAN MEMBACA PEMAHAMAN DI KELAS IV SDN LIDAH KULON 4 SURABAYA - Zakiyatur Rosyidah, Siti; ISNAINI DAMAYANTI, MARYAM (PGSD FIP UNESA, 2018)
Abstract The purpose of this research is to know the effectiveness of Directed Reading Thinking Activity (DRTA) strategy in reading comprehension learning in fourth grade about SDN Lidah Kulon 4 Surabaya. The type of research used an experimental design of pre-experimental design with one group pretest-posttest design. The sample of this research is students of class IV-B SDN Lidah Kulon 4 Surabaya. The result of research is proven by pretest-posttest hypothesis test of 6 with significant value 0,05. From this it can be said tcount (6)> ttable (2.064), it can be stated that H0 rejected and Ha accepted meaning that is an effective DRTA strategy used in learning comprehension reading in class IV SDN Lidah Kulon 4 Surabaya. Keywords: DRTA strategy, reading comprehension skill.